The Dynamics of Madrasas Development in Pekalongan City in the New Order Era during the PELITA V Period - Prayogi, Arditya; Fasya, Adib ‘Aunillah; Nasrullah, Riki (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
Education development is one of the important things carried out by a government. In this case, madrasas are no exception as one part of educational development. In this case, this article aims to reconstruct the history of madrasa development by utilizing quantitative data available in Pekalongan City during the Pelita V era (1989-1994). Pekalongan City itself is an important city that was once the capital of the Pekalongan Residency which was projected as a trading city where the educational aspect was important to build. This article was written using the historical method with stages of heuristics, criticism, interpretation and historiography. From the results of the study, it was found that the condition of madrasas in Pekalongan City in Pelita V, seen from the aspect of the number of schools, teachers and students, generally experienced fluctuations/dynamics. In this case, the construction of Madrasas at the elementary level (MI) at PELITA V in Pekalongan City is progressing well, although there is inequality, especially in the number of teachers. At the secondary level, both junior and senior (MTs and MA), madrasa development has increased and has had an impact on increasing educational participation.